Scots lovage, Ligusticum scoticum, is spreading in the Åland Islands, SW Finland - von Numers, Mikael; Hæggström, Carl-Adam; Hæggström, Eeva; Franzén, Helene; Franzén, Johan; Carlsson, Ralf (Memoranda Societatis pro Fauna et Flora Fennica, 2009)
Scots lovage, Ligusticum scoticum L., was probably collected already in 1892 in the Åland Islands, but it was not reported from Åland until 1970. Since then, the species has been found in an increasing number of localities. Here we report about 25 new localities found 1992–2008. There seemto be two centres for the species, one in thewesternmost islands of Åland, between the mainland of Eckerö and the Signilskär archipelago, and the other in the northern islands of Föglö.Amore systematic investigation in the archipelagos of Åland could yield new localities.